Sustainability Assessment of a Special Water Management Practice in a Hungarian River Basin - Hancz, Gabriella (International Journal of Engineering and Management Sciences, 2017)
The purpose of the study is to assess the sustainability of the current water management practice of thermal water usage for bathing. The methodological approach is material flow analysis since it allows to achieve results without regular or online measurements. The current river base management plan recorded the quality status of certain reaches of river Kösely and its tributaries - the receiving water bodies of the used thermal waters - regarding salt content as good and moderate. The ecological status is recorded as moderate and weak, respectively. Since the Water Framework Directive prescribes to achieve the goal of good ecological status, water management measures must be implemented to meet this objective. Since there is no BAT for salt removal from used thermal waters, the possibility to reduce salt loads remain the only feasible measure. The purpose of the study in the frame of a PhD study was to assess with calculations the yearly variations of water and salt flow in river Kösely and its tributaries in order to assess the sustainability of the practice of thermal water management in the river catchment. The result of the calculations is a flow scheme provided with numerical data of yearly water- and salt flow and a subsequent calculation of necessary rate of reduction of usage and discharge of thermal water